Blended Learning: Solusi Mengatasi Learning Loss dalam Pembelajaran - Nova Sukmawati Muskita; Vivi Monica Ramadhani; Adelfia Sallo' Padidi; Dewi Nurrochmah; Pintaka Kusumaningtyas (SAP (Susunan Artikel Pendidikan), 2022)
Learning loss due to online learning during the Covid-19 pandemic has occurred at all levels of education, from primary to secondary education. The purpose of this literature review is to discuss the implementation of the blended learning to overcome the symptoms of learning loss at the elementary (SD) to secondary (SMP and SMA) levels. This study aplies the literature review method to synthesize several published articles relating to the application of the blended learning at the elementary, junior, and high school levels. The results of the literature study were then analyzed to determine the benefits of the blended learning to overcome the symptoms of learning loss. The results of the study confirm that the blended learning can encourage students to study independently, motivate students by utilizing internet-based technology, as well as increase student learning activities and make it easier for students to find various learning materials from virtual sources. The implementation of blended learning is able to balance the collaboration between online and offline (face-to-face) learning that mutually reinforce each other to improve student learning outcomes that have not been achieved due to learning loss at all levels of education.